Beauty and the Beast of Paradise Lost. 1 - Yuki, Kaori (Kodansha Comics, 2021)
"Young and rambunctious Belle insists on going out to play in the forbidden woods, but her adventurous streak abruptly ends when her mother is spirited away by a beast known to kidnap beautiful women. Twisted by the loss of his wife, Belle's father keeps his daughter...locked away.... Finally emerging after years of solitude, Belle ventures back into the woods where she lost her mother and encounters the beast once more"--